Disclosing the generic behavior of topological solutions: An orbit-based approach - Arroyo Meza, L. E. [UNESP]; Dutra, Alvaro de Souza [UNESP]; dos Santos, J. R. L.; Hott, M. B. [UNESP]; Winter, O. C. [UNESP] (Epl Association, European Physical Society, 2012)
In this work we present a method, based on the vacuum structure of the potential for a system of two nonlinearly coupled scalar fields in 1+1 space-time dimensions, which yields complete information about the behavior of the topological configurations. This is done by means of an analysis of the orbits and the position of the degenerate vacua of the model on the configuration space. Copyright (C) EPLA, 2012